To solve the equation 3y - 5(2y - 4) = 62, we can follow the order of operations (PEMDAS/BODMAS). Let's simplify step by step:
First, distribute the -5 to the terms inside the parentheses:
3y - 5(2y - 4) = 62
3y - 10y + 20 = 62
Combine like terms:
-7y + 20 = 62
Next, isolate the variable term by moving the constant term to the other side:
-7y + 20 - 20 = 62 - 20
-7y = 42
Now, divide both sides by -7 to solve for y:
(-7y)/(-7) = 42/(-7)
y = -6
Therefore, the solution to the equation is y = -6.
Saw the following Winery equation 3y - 5 (2y - 4) = 62
1 answer